THE CORRELATION BETWEEN VOCABULARY SIZE AND THE READING COMPREHENSION OF THE ENGLISH EDUCATION DEPARTMENT STUDENTS - Cinthia Astan; Siti Mina Tamah (Magister Scientiae, 2015)
The study explored the correlation between vocabulary size and the three levels of reading comprehension namely literal, inferential, and critical reading comprehension. The main intention was to discover what the correlation was between vocabulary size and literal reading comprehension, inferential reading comprehension, and critical reading comprehension in terms of direction and magnitude. The subjects were 30 students of the English Department at a university in Surabaya. A Vocabulary Size Test and a Reading Comprehension Test were administered to measure the subjects' vocabulary size and reading comprehension performance. The findings revealed that vocabulary size was positively, strongly, and significantly correlated to literal reading comprehension, inferential reading comprehension and critical reading comprehension.